Global food and energy price volatility: Implications for Rwanda - Ngabitsinze, Jean Chrysostome (2022)
Jean Chrysostome Ngabitsinze POLICY SEMINAR Retail food prices at the country level and implications for food security How are rising food prices, further aggravated by the invasion of Ukraine, being transmitted at the country level? MAR 29, 2022 - 9:30 TO 11:00AM EDT